Epoxy-steel fiber composites : a simple model to predict the fiber sedimentation - Leite, Janaina L. (2010)
Sedimentation of short steel fibers (SSFs) is an important phenomenon observed in the manufacture by casting of polymer/metal composites. Modeling of the fiber sedimentation has been a subject of research but hardly applied in the context of injection molds. In this study, the sedimentation velocity of the SSF suspension in nonreactive epoxy resin was evaluated theoretically and experimentally. The sedimentation behavior of single and concentrated SSF in epoxy resin was followed experimentally to obtain the terminal and sedimentation velocities. These data were interpreted using theoretical models that take into account the hindered settling factor and the shape factor. The experimental data can be correlated with the theoretical analyses. The findings were used to propose a simple model to predict the sedimentation of steel fibers in viscous resins that are used in composites for making molding blocks.